Assessing Balâghah Learning Outcomes: A Comparative Evaluation of Fourth Grade Students - Alfarisi, Muhammad Hanif; Wati, Ana Taqwa; Bakti, Anugrah Arya; Iqbal, Mochammad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to determine whether there is a difference between the achievement of learning balaghah between fourth grade students of Kulliyyatul Muallimin Al-Islamiyyah Pondok Modern Darussalam Gontor, Central Campus and Campus Three and to find out whether the difference is significant or not. The research approach used in this study is quantitative research using inferential quantitative methods. The data analysed in this study is the learning achievement of balâghah fourth grade students of Pondok Modern Darussalam Gontor Central Campus and Campus Three. The population in this study were all fourth grade students of Pondok Modern Darussalam Gontor Central Campus and Campus Three. Based on the results of the T test of two independent samples, it shows that t count (12.940) is smaller than t table (1.966) and the significance value is smaller than alpha (0.05). So the researcher can conclude that there is a significant difference between the balâghah scores of fourth grade students of Kulliyyatul Muallimin Al-Islamiyyah Pondok Modern Darussalam Gontor Central Campus and Campus Three. With an average value (7.9018), the balâghah learning achievement of fourth grade students of Kulliyyatul Muallimin Al-Islamiyyah Pondok Modern Darussalam Gontor Central Campus is higher than the average balâghah score of fourth grade students of Campus Three (6.2068).